Why understanding the pioneering and continuing contributions of BIOCLIM to species distribution modelling is important - Booth, Trevor H. (Austral ecology, 2018)
Modern species distribution modelling (SDM) began in 1984 with the launch of the BIOCLIM program in Australia. With more than 900 papers mentioning ‘species distribution model’ published around the world to date, SDM is one of the most active areas of global ecology. Three books published in 2009, 2011 and 2017 have reviewed SDM, and the closely related areas of ecological niche modelling and habitat suitability modelling. All three books provide excellent introductions to these topics, but give very little information on the role that BIOCLIM played in laying the foundation for these research areas. Understanding the history of BIOCLIM is vital because it was the first package to implement the basic SDM process in an easy‐to‐use integrated system. It provided what are still the most commonly used set of 19 bioclimatic variables and contributed to the development of the interpolation routines used to prepare the most commonly used source of bioclimatic data (WorldClim). Early BIOCLIM studies investigated important issues such as ecological niche, invasion risk, conservation planning and impacts of climate change. Although all three books acknowledge that the BIOCLIM package was important in early SDM research, they all deal with the pioneering work very briefly and omit important details which are described here. Virtually all current SDM studies owe something to the pioneering BIOCLIM work, but this is rarely acknowledged.